2011
DOI: 10.1523/jneurosci.3118-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Contributes to Kindled Seizure Development in Pentylenetetrazole-Treated Mice by Converting Pro-BDNF to Mature BDNF in the Hippocampus

Abstract: (Ϫ/Ϫ) mice compared with wild-type mice, an observation that was accompanied by decreased hippocampal levels of mature brain-derived neurotrophic factor. Microinjecting the BDNF scavenger TrkB-Fc into the right ventricle before each PTZ treatment significantly suppressed the development of kindling in wild-type mice, whereas no effect was observed in MMP-9 (Ϫ/Ϫ) mice. On the other hand, bilateral injections of pro-BDNF into the hippocampal dentate gyrus significantly enhanced kindling in wild-type mice but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 56 publications
7
149
0
Order By: Relevance
“…In parallel to these findings Mizoguchi et al provided additional data suggesting that mossy fiber sprouting induced by repeated PTZ treatment was reduced in MMP-9 null mice compared to wild type mice, suggesting that increased hippocampal MMP-9 activity is associated with sprouting of mossy fibers (23). Besides, the previous studies have also revealed that several MMPs are acutely upregulated after status epilepticus (12).…”
Section: Acknowledgmentsmentioning
confidence: 74%
See 1 more Smart Citation
“…In parallel to these findings Mizoguchi et al provided additional data suggesting that mossy fiber sprouting induced by repeated PTZ treatment was reduced in MMP-9 null mice compared to wild type mice, suggesting that increased hippocampal MMP-9 activity is associated with sprouting of mossy fibers (23). Besides, the previous studies have also revealed that several MMPs are acutely upregulated after status epilepticus (12).…”
Section: Acknowledgmentsmentioning
confidence: 74%
“…There are convincing preclinical studies demonstrating that the expression and activity of MMP-9 is regulated by repetitive activation of NMDA receptors (23). In fact, the inhibition of NMDA receptors prevented PTZ-induced convulsions and kindling (9).…”
Section: Mmp-9 (23)mentioning
confidence: 99%
“…Gel zymography was performed to evaluate the activities of MMP-2 and MMP-9. Sample preparation was done as previously described by Mizoguchi et al (34). Samples were run on SDS-PAGE (10%) gels that contained 0.1% gelatin under non-reducing conditions.…”
Section: Reagentsmentioning
confidence: 99%
“…Since the present data showed that increases of m-BDNF and furin concomitant with a decrease of p-BDNF occurred in both the normal and post-ischemic DG tissues in response to the two agonists, it is probable that GPR40 activation stimulated furin to cleave p-BDNF to m-BDNF intracellularly. Likewise, p-BDNF might be secreted extracellularly and might be cleaved by metalloproteinases and/ or plasmin to m-BDNF [11,33]. Among four possible proteolytic enzymes that can be involved in p-BDNF cleavage including furin, proconvertases, metalloproteinases and plasmin, the strongest candidate that can be activated by PUFA-GPR40 signaling may be furin.…”
Section: Discussionmentioning
confidence: 99%